Bisphenol A: A notorious player in the mosaic of autoimmunity. (17th November 2018) - Aljadeff, Gali; Longhi, Eleonora; Shoenfeld, Yehuda
Abstract: The multifactorial etiology of autoimmune diseases has been studied at large. Genetic risk factors and environmental agents play an integral role in the pathogenesis of autoimmune processes. In recent decades, Bisphenol A (BPA), an exogenous compound found in polycarbonate plastic, has gained attention for its harmful multifocal effects on a diverse subset of systemic pathways, potentially contributing to disease onset and exacerbation. BPA is a xenoestrogen used globally in the manufacture of daily use products including plastic storage containers, water and infant bottles, and food and drink packaging. BPA exhibits immune stimulatory activity bringing into question the association between its greater global presence and the increased prevalence of autoimmune diseases. The purpose of this multi-study analysis is to assess recent research investigating the underlying role of BPA in autoreactive mechanisms. Although research at present does not directly link BPA exposure to the development of autoimmune diseases, a large body of evidence supports the pro-inflammatory effects of BPA on the immune system. Further studies are required to elucidate the role of BPA in autoimmune pathogenesis, however caution should be taken in the use of BPA containing products by those affected or genetically susceptible to developing autoimmune diseases.